True Intellectual, or Thin-Legged: Image of Intellectual According to Lexicographical Sources - A. V. Shchetinina (Научный диалог, 2018)
The article considers the language image of the intellectual on the basis of the data presented in the explanatory dictionaries, including the dictionaries of jargon and Russian folk dialects. It is noted that the uniqueness of the concept of “intellectual” causes the complexity of the dictionary definition. As a result of the analysis of definitions of the word intelligent it is established that in lexicographical sources there is no uniformity in interpretations: usually the word is presented as a monosemant in which meaning the belonging of the person to a certain social group is fixed, in other cases belonging to group and at the same time some personally significant qualities are specified. It is emphasized that in order to list all the qualities recorded in the dictionaries, it is necessary to refer to different sources, in which complementary information is presented. Summarizing these dictionaries, the author formulates three literary meanings, on the basis of which different images of the intellectual are formed: as a representative of the class of intelligentsia; as a person endowed with positive moral qualities regardless of belonging to a social group; as a person belonging to the class of intelligentsia, but possessing negative characteristics (lack of will, adaptability, etc.). It is shown that according to the materials of dialect and slang dictionaries the image of an intellectual can be interpreted in the aspect of the semantics of exclusivity as a person, for various reasons alien to the society of criminals and traditional peasant society.